2019
DOI: 10.2147/ccid.s191935
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of the efficacy of a new hyaluronic acid gel on dynamic and static wrinkles in volunteers with moderate aging/photoaging</p>

Abstract: PurposeAim of the study was to determine both clinically and by noninvasive instrumental evaluations the efficacy, tolerability and the duration of the effects of a new hyaluronic acid (HA) gel in human volunteers with moderate aging/photoaging.Patients and methodsEighteen volunteers (35–55 years) were enrolled in this single-center study. The subjects underwent five visits. The first visit was at baseline to determine the adherence to the inclusion criteria, followed by the first injection of the HA-based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…Patients mean age was 43,3±7,7 years (31-56). Time elapsed between subsequent administrations averaged 4.3±0.47 weeks (4)(5). We investigated the patients' lifestyle, asking questions about sun exposure habits, smoking, sports activities, any previous and current disease and pharmacological therapies: 5 out of 10 patients (50%) were smokers, with an average consumption of 10 cigarettes per day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients mean age was 43,3±7,7 years (31-56). Time elapsed between subsequent administrations averaged 4.3±0.47 weeks (4)(5). We investigated the patients' lifestyle, asking questions about sun exposure habits, smoking, sports activities, any previous and current disease and pharmacological therapies: 5 out of 10 patients (50%) were smokers, with an average consumption of 10 cigarettes per day.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with atrophic acne scars, therapy can lead to improved scar appearance, skin texture, and patient satisfaction. 4,5 To date there are no published data about the combination of PRP and HA applied topically on the face to correct the signs of ageing, neither papers where topical PRP is associated to microneedling to rejuvenate the facial skin. The only published data in which PRP is used topically to improve face appearance in healthy volunteers is from Yuksal et al, who obtained a significant improvement in the patients' auto-evaluation rate, but the medical assessment showed a significant difference only for firmness-sagging.…”
Section: Introductionmentioning
confidence: 99%
“…Aging/photoaging grade and surface microrelief improved 2 months after the first injection procedure. The treatments were very well tolerated by the volunteers as determined by the self-grading score [121]. Lee et.al, 2019 reported that Cross-linked hyaluronic acid (CLHA) patches were not an irritant, whereas a clinical study showed that application of single CLHA patches significantly improved skin hydration at the periorbital region for 3 days and at the nasolabial fold for 6 days.…”
Section: F Hyaluronic Acidmentioning
confidence: 99%
“…Aging/photoaging grade and surface microrelief improved 2 months after the irst injection procedure. The treatments were very well tolerated by the volunteers as determined by the self-grading score [209]. Lee et al, 2019 reported that Cross-linked hyaluronic acid (CLHA) patches were not an irritant, whereas a clinical study showed that application of single CLHA patches signi icantly improved skin hydration at the periorbital region for 3 days and at the nasolabial fold for 6 days.…”
Section: Astaxanthinmentioning
confidence: 99%